2012
DOI: 10.1177/193229681200600603
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Noninvasive Clinical Measurement of Lens Autofluorescence and Rayleigh Scattering Using a Fluorescence Biomicroscope

Abstract: Abbreviations: (AGE) advanced glycation end product, (IR) infrared, (DFA) 1-deoxyfructosyl glycation adduct, (LED) light-emitting diode, (UV) ultraviolet Keywords: advanced glycation end products, biomicroscope, diabetes mellitus, fluorescence ratio, lens autofluorescence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…Freedom Meditech, Inc has received US marketing clearance for a scanning confocal biomicroscope that rapidly measures lens autofluorescence without dilation of the pupils. 15 Our previous study of lens autofluorescence of 127 subjects with healthy eyes who had not been diagnosed with diabetes showed a linear relationship of lens autofluorescence with the age of the subject, 15 a result consistent with previous reports. 3,6,16 We wish to investigate 2 possible clinical uses of our instrument: (1) to identify subjects with undiagnosed type 2 diabetes and (2) to measure lens autofluorescence as a marker for the progression of diabetes.…”
Section: Original Articlesupporting
confidence: 90%
“…Freedom Meditech, Inc has received US marketing clearance for a scanning confocal biomicroscope that rapidly measures lens autofluorescence without dilation of the pupils. 15 Our previous study of lens autofluorescence of 127 subjects with healthy eyes who had not been diagnosed with diabetes showed a linear relationship of lens autofluorescence with the age of the subject, 15 a result consistent with previous reports. 3,6,16 We wish to investigate 2 possible clinical uses of our instrument: (1) to identify subjects with undiagnosed type 2 diabetes and (2) to measure lens autofluorescence as a marker for the progression of diabetes.…”
Section: Original Articlesupporting
confidence: 90%
“…Lens fibers are free from organelles, and lens proteins within these fibers, such as crystallins (α, β and γ) are long‐lived, which facilitates the accumulation of AGEs throughout life . This accumulation is assumed to contribute to the gradual decrease in tissue and organ function observed with aging . All crystalline species show tryptophan fluorescence (excitation maximum at 290 nm and emission maximum ~340 nm) and their distribution is uniform throughout lens cross‐sections, as is the distribution of protein …”
Section: Ocular Endogenous Fluorophoresmentioning
confidence: 99%
“…In addition to age‐related changes in light transmission, several studies have revealed an increase in fluorescence and a decrease in transmission with certain conditions, such as diabetes . Several studies have reported that lens AF is higher in diabetic patients than in healthy subjects, and that lens transmission in subjects of about the same age was higher in diabetic patients than in healthy subjects …”
Section: Ocular Af In Diabetesmentioning
confidence: 99%
“…26 One physiological aspect has to be particularly taken into account when measuring lens AF: The age-related opacification of the lens is part of the nonenzymatic glycation of the lens proteins and the degree of the glycation process (that can be assessed by measurements of the lens AF) reflect partly this physiologic process and can be exacerbated in the presence of hyperglycemia. [27][28][29][30] In this issue of the Journal of Diabetes Science and Technology, Cahn et al present data from a study aiming at investigating possible uses of a new scanning confocal biomicroscope to identify subjects with undiagnosed type 2 diabetes.…”
mentioning
confidence: 99%
“…Since lens AF physiologically increases with age, 30 all comparisons were performed with an age-adjusted lens AF value of healthy subjects. At a defined threshold (fluorescence deviation of 2500 counts above the value of age-matched healthy controls), the authors report for their method a sensitivity and a specificity (67% and 94%, respectively) for identifying subjects with type 2 diabetes that is comparable to that of glucose threshold tests.…”
mentioning
confidence: 99%